Twice in a lifetime [videorecording (DVD)] - Hackman, Gene; Ann-Margret, 1941-; Burstyn, Ellen, 1932-; Madigan, Amy; Metheny, Pat; Welland, Colin; Yorkin, Bud, 1926-2015 (Warner Home Video, 2005)
"Harry and Kate Mackenzie married for better or worse and after 30 years, their union is neither better nor worse. Instead, it somehow simply died. But Harry has a second chance in life. He's met a woman who rekindles his sense of life's fullness. But Harry knows taking that chance will cause his family pain"--Container.